2021
DOI: 10.1186/s13068-021-02077-8
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a tunable promoter library to optimize gene expression in Methylomonas sp. DH-1, a methanotroph, and its application to cadaverine production

Abstract: Background As methane is 84 times more potent than carbon dioxide in exacerbating the greenhouse effect, there is an increasing interest in the utilization of methanotrophic bacteria that can convert harmful methane into various value-added compounds. A recently isolated methanotroph, Methylomonas sp. DH-1, is a promising biofactory platform because of its relatively fast growth. However, the lack of genetic engineering tools hampers its wide use in the bioindustry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…A recent report showcased the strength of constitutive promoters such as P DnaA (2.81-fold), P Integrase (3.45-fold), P rpmB (22.09-fold), P (2Fe–2S)-binding protein (41.54-fold) using GFP as reporter protein in Methylomonas sp. DH-1 ( Lee et al, 2021 ). P sps earlier studied by our group ( Awasthi et al, 2022 ) is shown to efficiently perform 2.5-fold increase in gene expression, in this work.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showcased the strength of constitutive promoters such as P DnaA (2.81-fold), P Integrase (3.45-fold), P rpmB (22.09-fold), P (2Fe–2S)-binding protein (41.54-fold) using GFP as reporter protein in Methylomonas sp. DH-1 ( Lee et al, 2021 ). P sps earlier studied by our group ( Awasthi et al, 2022 ) is shown to efficiently perform 2.5-fold increase in gene expression, in this work.…”
Section: Discussionmentioning
confidence: 99%
“…So far, diversified promoter libraries have been built to evaluate promoter candidates. The original method of building a library is to amplify the promoters of all genes and detect the interaction with proteins by 2D-PAGE, then further screen through fusing fluorescent proteins in vivo (Lee et al 2021 ). However, the tedious process greatly increases the time cost in this way.…”
Section: Promoter Engineeringmentioning
confidence: 99%
“…Rational regulation of gene expression by appropriate promoters is crucial for the efficient production of target products in industrial microorganisms. [ 4 ] Various methods, such as error‐prone PCR, [ 5 ] transcriptome data analysis, [ 6 ] promoter rational design, [ 7 ] have been employed to establish promoter libraries in different bacteria and fungi, which include Methylomonas , [ 8 ] Rhodobacter sphaeroides , [ 9 ] Myxobacteria , [ 10 ] Saccharopolyspora erythraea , [ 11 ] Burkholderiales , [ 12 ] Saccharomyces cerevisiae , [ 13 ] Aspergillus nidulans , [ 14 ] Aspergillus oryzae , [ 15 ] and Trichoderma reesei . [ 16 ] The availability of diverse promoters broadens the potential applications of microbial genetic modification, [ 15 ] such as expressing and screening a single gene to obtain optimal expression intensity and corresponding high‐yield strain.…”
Section: Introductionmentioning
confidence: 99%